New records of Neopetrosia carbonaria (Lamarck, 1814) from the Brazilian coast reveal new morphological features and spicule types - Sandes, Joana; Rocha, Lívia; Pinheiro, Ulisses; Santos, George Garcia (Zootaxa, 2023)
Sponges of the family Petrosiidae have usually a stony and brittle texture due the high silica content of the mineral skeleton that is formed by a more-or-less regular isotropic reticulation of undefined primary and secondary tracts. Neopetrosia species are distributed worldwide and twelve species are found in the Tropical Western Atlantic Ocean, of which four are recorded from the Brazilian coast. Here, we describe new Neopetrosia carbonaria specimens from several localities along the NE Brazilian coast, analyze the Neopetrosia carbonaria holotype and review the previous record of N. carbonaria from the Brazilian coast. Our study reveals new morphological features and spicule types in the Brazilian populations of N. carbonaria. Now, Neopetrosia carbonaria is defined by a thick encrusting to repent or ramose sponge, with reddish brown to brown color or dark green to black color in vivo, two categories of oxeas as megascleres and raphidiform toxas as microscleres. These toxas are quite rare and occur in both black and brown sponges. Due the absence and rarity of raphidiform toxas in some specimens, unrelated to its color, we assume that these differences are intraspecific. However, we suggest that all records of Neopetrosia carbonaria should be reevaluated, since toxas can be easily overlooked, added to the use of molecular methods to investigate the relationship between the Caribbean and Brazilian populations.